Desenvolvimento de baixo impacto aplicado ao processo de planejamento urbano - Tavanti, Débora Riva (2009)
Urbans areas even biggens are becoming impermeabilized reducing the soil`s infiltration rate and increasing the velocity and volume of runoff, changing meaningly the hydrological cycle and causing floods. A set of techniques able to create hydrologically functional landscape can be found at Low Impact Development (LID) that works just similar to the natural, becoming possible the development of projects adapted to the natural topography, maintaining the yield of the lot and the local hydrological function; aiming at esthetics valorization and stormwater control management with low cost. This study makes use of this methodology since the beginning of the planning process, working at the some time with urban, environmental and hydrological aspects, intending to recuperate or even to keep the pre-development behavior of the area. To support the local hydrology, reduce sealing, keeping time to concentrate, to keep Fingerprinting, enhance infiltration, among others. It compares the predevelopment conditions, the conventional urbanization and that with LID techniques related to aspects mentioned to a specifc area at UFSCar Campus, São Paulo. This search revealed that is possible to have an urban planning using LID, with urban, environmental and hydrological advantages in the opposite to the conventional development systems, such as the increase of permeable areas, vegetation areas and the reduction of peak discharge and stormwater runoff. Low impact development makes these interventions in a simultaneous way just to re-establish the pre-existents conditions, and then to make use of integrated management`s practice.